PENDAMPINGAN PENCATATAN DAN PENYUSUNAN APLIKASI LAPORAN KEUANGAN MASJID AL MANAR MERAUKE BERDASARKAN ISAK 35 - Agus Nisfur Romdioni; Candra Agus Wahyudi (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2023)
This Community Service Activity aims to provide training for the management of the Al Manar mosque in Kampung Kuper, Semangga District, Merauke Regency related to Providing knowledge on how to prepare mosque financial reports using an Excel-based application for financial reporting, and assistance to mosque administrators in compiling mosque financial reports based on ISAK 35 as the responsibility of the task in accordance with the mandate carried out. This activity was carried out in the form of training and assistance in making mosque financial reports with the application of systematic financial reports using the Microsoft Excel program. The methods for implementing this service program are: Field Observations, Implementation of Training Programs, and Evaluation. The results of the community service activities that have been carried out can be drawn several conclusions, namely (1) With the existence of training and assistance in the preparation of financial reports in accordance with financial accounting standards based on the excel program, it is able to improve mosque administrators in compiling financial reports; (2) Having an accounting program with excel can help make it easier to prepare financial reports; (3) With assistance in compiling financial reports, skills and accuracy in preparing financial reports can be increased.